Classification and Interpretation for 11 FBN1 Variants Responsible for Marfan Syndrome and Pre-implantation Genetic Testing (PGT) for Two Families Successfully Blocked Transmission of the Pathogenic Mutations - Chen, Songchang; Fei, Hongjun; Zhang, Junyun; Chen, Yiyao; Huang, Hefeng; Lu, Daru; Xu, Chenming (Frontiers in Molecular Biosciences, 2021)
Background：Lifespan of Marfan Syndrome (MFS) patients is shortened especially patients without early diagnostics, preventive treatment and elective surgery. Clinically, MFS diagnosis mainly dependent on phenotypes, but for children, sporadic cases or suspicious MFS patients, molecular genetic testing mainly FBN1 mutation screening plays a significant role in the diagnosis of MFS. PGT-M gives couples which had family history of monogenic disorders the opportunity to avoid the occurrence of MFS. Methods：11 families with MFS were recruited and collected complete clinical features in this study. Variants were classification and interpretation through pedigree analysis according to guidelines. Two families choose to underwent PGT-M, 16 blastocysts were biopsied and amplified. Haplotype analysis was performed to deduce embryo’s genotype by using single nucleotide polymorphisms (SNPs) identified in each sample. Results：We identified 11 potential disease-causing FBN1 variants, and 6 of them are novel. All variants were assessed with prediction tools to assess mutation pathogenicity, population databases to evaluated population allele frequency, literature databases to identify had the variant been reported in MFS patients and multiple sequence alignment to do conservative analysis, finally, 9 variants were classified as likely pathogenic/ pathogenic variants. Among 11 variants, 8 variants were missense, and 7 of them located in the Ca-binding EGF-like motifs, moreover, half of them substituted conserved Cystein residues. We also identified a splice site variant, a frameshift variant and a synonymous variant. There are 2 variants are de novo variants. PGT-M help two MFS families give birth to a healthy baby not carry FBN1 mutation. Conclusions：In the present study, FBN1 mutation spectrum was enriched, and may help further elucidate the pathogenesis, benefiting clinical diagnosis and management of MFS. We make use of a reliable PGT-M method to give birth to healthy baby for 2 MFS families successfully.